Strategi Pengembangan Sumber Daya Manusia Melalui Pendidikan dan Pelatihan pada Kantor Dinas Tenaga Kerja Kota Makassar - Putri Anna Nirwan (Universitas Negeri Makassar, 2020)
This study aims to determine the strategy of developing human resources through education and training at the Makassar City Manpower Office. Using a qualitative descriptive approach. The main instrument in this study is the researcher himself using a cellphone, and using a field note that is by recording data related to research found in the field. Data collection was carried out by using observation, interview, and documentation techniques. Analysis of the data used is data reduction, data presentation and conclusions. The results showed that the strategy of developing human resources through education and training at the Makassar City Manpower Office was in a fairly good category, seeing the focus in this study, namely: 1) determining needs has been determined quite well, 2) determining targets that are in in the good enough category, 3) the determination of the program content is in the good enough category, 4) the principles of learning get pretty good results, 5) the implementation of the program gets pretty good results, 6) identification of the benefits of getting pretty good results, and 7 ) the evaluation of program implementation got quite good results